ANALISIS KETIMPANGAN PENDAPATAN ANTAR WILAYAH KECAMATAN DI KABUPATEN SITUBONDO TAHUN 2016 - Karnadi Karnadi; Lita Permata Sari (Growth, 2017)
Economic growth between different regions may have an impact on the uneven distribution of income and development. Situbondo Regency which has an area of ​​163,850 Ha, has 17 districts. The sub-districts in Situbondo District have different areas, natural potential, and different regional characteristics. Inequality income is a problem that can be found in any region. In general, inequality can not be destroyed, but can only be reduced to an acceptable level by a particular social system so that alignment in the system is maintained in the process of growth. Implementation of regional autonomy is expected local government able to manage regional potency maximally so that inequality of economic development, yield and income received by sub-district decreasing. This research uses williamson index analysis to measure income inequality between districts in Situbondo Regency in 2016. The result shows Williamson index value of 0.16, that is still far categorized as lame, economic growth in Situbondo Regency is still said to be evenly distributed.